Efficacy and Toxicity of Hypofractionated Palliative Radiotherapy for Breast Cancer Patients with Skin Invasion - Talha Maqsood; Adnan Zeb; Zeeshan Ahmed Alvi; Sameed Hussain; Muhammad Imran Wajid; Omer Riaz (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the efficacy and toxicity of palliative radiotherapy for locally advanced breast cancer patients with skin invasion.